Pediatric laryngeal cleft repair with coblation: Functional comparison of a novel technique with traditional methods. (December 2022) - Shah, Hemali P.; Brawley, Craig Cameron; Maurrasse, Sarah; Schumacher, Jane; Ganesh, Meera; Thompson, Dana Mara; Ida, Jonathan; Valika, Taher
Abstract: Objectives: The traditional endoscopic techniques for surgical management of laryngeal clefts are carbon dioxide (CO2 ) laser or microlaryngeal instruments (cold steel). This study compares the functional efficacy and safety of coblation, or "cold" radiofrequency ablation, to traditional approaches for endoscopic laryngeal cleft repair. Methods: Patients who underwent endoscopic laryngeal cleft repair with CO2 laser, cold steel, or coblator at two tertiary academic centers from 2015 to 2021 were retrospectively identified. The primary outcome studied was swallowing function: pre- and postoperative swallow studies were scored according to the International Dysphagia Diet Standardization Initiative with higher scores indicating worse swallow function. Secondary outcomes included surgical complications and rates of dehiscence. Results: Of the 53 patients included, 14 underwent repair with CO2 laser, 23 with cold steel, and 16 with the coblator. Mean age at surgery was 2.2 ± 1.1 years for the laser group, 4.3 ± 4.0 years for cold steel, and 1.9 ± 1.4 years for the coblator group. In the laser group, 100% of clefts were type I; for the cold steel group, 82.6% of clefts were type I and 17.4% were type II; for the coblator group, 93.8% of clefts were type I and 6.3% were type II. Pre- and postoperative swallow study scores were 6.3 ± 2.8 and 4.3 ± 3.2, respectively, (p = 0.001) for the laser group, 6.9 ± 2.8 and 5.3 ± 3.1 (p = 0.071) for the cold steel group, and 7.5 ± 1.5 and 4.0 ± 2.9 (p < 0.001) for the coblator group. Mean change in swallow study scores were similar across the three groups (p = 0.212). No patients experienced postoperative dehiscence at the surgical site or complications; no revisions were required. Conclusions: Cleft repair with the novel coblation technique showed significant improvements in swallow study scores without any occurrences of postoperative dehiscence or revisions. Coblation is a safe and efficacious approach for laryngeal cleft repair. Highlights: Coblation is a novel emerging technique for laryngeal cleft repair. Laryngeal cleft repair with coblation demonstrates improvement in swallow function. No patients experienced postoperative dehiscence at the surgical site after repair. Coblation is a safe, efficacious approach for cleft repair with promising results.